2000
DOI: 10.1177/0003489400109s1209
|View full text |Cite
|
Sign up to set email alerts
|

Shaw Scalpel in Revision Cochlear Implant Surgery

Abstract: The use of traditional electrocautery is prohibited in revision or replacement cochlear implant surgery because of the concern for end organ tissue damage. Additionally, electrical current spread to the malfunctioning device could interfere with an accurate cause-of-failure analysis. Clinical reports have confirmed the utility of the Shaw scalpel for dermatologic, ophthalmic, and head and neck surgery. The Shaw scalpel is a thermally activated cutting blade that provides a bloodless field through immediate cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Incision and elevation of the skin flaps were performed with the Shaw heated scalpel (Hemostatix Medical Devices, Cherry Hill, NJ) instead of monopolar cautery. 7 In most instances, an inverted‐J incision was used. Monopolar cautery should not be used with an implant in place because the electrical current can damage the implant, precluding proper integrity testing, and can also be carried along the implant directly into the cochlea with damage to the remaining neurons.…”
Section: Methodsmentioning
confidence: 99%
“…Incision and elevation of the skin flaps were performed with the Shaw heated scalpel (Hemostatix Medical Devices, Cherry Hill, NJ) instead of monopolar cautery. 7 In most instances, an inverted‐J incision was used. Monopolar cautery should not be used with an implant in place because the electrical current can damage the implant, precluding proper integrity testing, and can also be carried along the implant directly into the cochlea with damage to the remaining neurons.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the temperature of the Shaw blade may be as high as 280°C and might melt the silicone covering of some cochlear implants. 1 Using Shaw blades was also found to be a significant risk factor for facial weakness during primary parotid surgery. 3 Therefore, caution is needed while working near important structures such as implants and nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In primary cochlear implantation all the electrocautery instruments have been turned off when the device is brought into the sterile field, but at that point of time hemostasis has already been achieved. 1 In revision cochlear implant surgery, when the implant is placed in the second ear or in patients with another electronic medical device, monopolar electrocautery is strictly contraindicated. 1 Furthermore, bipolar electrocautery within 5 cm of the cochlear implant is not allowed, because of the warranty regulation of the company.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations